Utilization of Instagram Social Media by Perumda Tirtanadi in Public Communication in North Sumatra - Tifani Alzahra; Muhammad Husni Ritonga (Ali Institute of Research and Publication, 2026)
This study aims to analyze the utilization of Instagram social media by Perumda Tirtanadi in public communication with the community in North Sumatra. This study employed a qualitative approach with a case study method. Data were collected through semi-structured interviews, non-participant observation of the Instagram account @tirtanadiprovsu, and documentation. The informants consisted of internal parties directly involved in managing Perumda Tirtanadi’s social media. Data were analyzed using the Miles and Huberman model and validated through source and method triangulation. The analysis applied Pierre Levy’s New Media Theory, particularly the aspects of social interaction and social integration. The results show that Instagram is utilized as a medium for delivering public information and facilitating two-way communication through comment features and direct messages (DM). Instagram is also used to build closer relationships with the community through the publication of service activities and social programs. However, several challenges remain, including inconsistencies in interaction management across branch accounts and the need to improve the visual quality of digital communication content. This study indicates that social media plays an important role in supporting public communication in public service institutions in the digital era.